Effects of a high-caloric diet and physical exercise on brain metabolite levels: a combined proton MRS and histologic study - Auer, Matthias; Ende, Gabriele; Gass, Peter (Journal of cerebral blood flow & metabolism, 2015)
Excessive intake of high-caloric diets as well as subsequent development of obesity and diabetes mellitus may exert a wide range of unfavorable effects on the central nervous system (CNS). It has been suggested that one mechanism in this context is the promotion of neuroinflammation. The potentially harmful effects of such diets were suggested to be mitigated by physical exercise. Here, we conducted a study investigating the effects of physical exercise in a cafeteria-diet mouse model on CNS metabolites by means of in vivo proton magnetic resonance spectroscopy (1HMRS). In addition postmortem histologic and real-time (RT)-PCR analyses for inflammatory markers were performed. Cafeteria diet induced obesity and hyperglycemia, which was only partially moderated by exercise. It also induced several changes in CNS metabolites such as reduced hippocampal glutamate (Glu), choline-containing compounds (tCho) and N-acetylaspartate (NAA)+N-acetyl-aspartyl-glutamic acid (NAAG) (tNAA) levels, whereas opposite effects were seen for running. No association of these effects with markers of central inflammation could be observed. These findings suggest that while voluntary wheel running alone is insufficient to prevent the unfavorable peripheral sequelae of the diet, it counteracted many changes in brain metabolites. The observed effects seem to be independent of neuroinflammation.